2017
DOI: 10.1002/acp.3373
|View full text |Cite
|
Sign up to set email alerts
|

Alcohol Intoxication and Metamemory: Little Evidence that Moderate Intoxication Impairs Metacognitive Monitoring Processes

Abstract: There is minimal research on metacognition in alcohol-intoxicated participants. Study 1 examined metacognition across sober, intoxicated, and placebo groups, with the intoxicated group's breath alcohol concentration reaching 0.074 g/ 210 L on average immediately prior to the metacognition task. Participants answered cued recall general knowledge questions and provided confidence ratings and feeling-of-knowing judgments. They then completed a recognition (i.e., multiple choice) version of the same task, indicat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
16
0

Year Published

2018
2018
2019
2019

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 13 publications
(18 citation statements)
references
References 53 publications
(69 reference statements)
2
16
0
Order By: Relevance
“…Participants, who had either consumed alcohol (BrAC 0.06%) or a placebo, studied unfamiliar faces and indicated for each face the likelihood that they would recognize the face on a future memory test. In line with previous findings, participants who were intoxicated did not perform worse on the face recognition test (e.g., Flowe et al, ) and gave similar judgments of learning (e.g., Evans et al, ).…”
Section: Experimental Studiessupporting
confidence: 90%
“…Participants, who had either consumed alcohol (BrAC 0.06%) or a placebo, studied unfamiliar faces and indicated for each face the likelihood that they would recognize the face on a future memory test. In line with previous findings, participants who were intoxicated did not perform worse on the face recognition test (e.g., Flowe et al, ) and gave similar judgments of learning (e.g., Evans et al, ).…”
Section: Experimental Studiessupporting
confidence: 90%
“…In verbal learning research, intoxicated participants respond more conservatively at test than placebo participants (Curran & Hildebrandt, ; Maylor, Rabbit, & Kingstone, ; Mintzer & Griffiths, , ), suggesting they are trying to compensate for expected alcohol‐related memory impairment. There is also basic cognitive research finding that while participants who are intoxicated compared with sober do not differ in judging the likely accuracy of their answers (Evans et al, ; Nelson, McSpadden, Fromme, & Marlatt, ), they have been found to make less accurate judgements of learning during encoding (Nelson et al, ). Findings are somewhat mixed, in the eyewitness/victim alcohol literature.…”
Section: Alcohol and Remembering Rapementioning
confidence: 99%
“…The final sample therefore comprised 210 participants; mostly female (56.66%) and Hispanic (66.19%; 10.95% African American; 10.95% White; 10.48% other; 1.43% did not respond), with ages ranging from 21 to 47 ( M = 24; Mdn = 23; SD = 5). Note, data collected from these participants have been reported elsewhere (Evans et al, ; Schreiber Compo et al, ), but other than demographic characteristics and manipulation checks the data presented here have not been published.…”
Section: Methodsmentioning
confidence: 99%